TINJAUAN FILSAFAT KEBUDAYAAN TERHADAP UPACARA ADAT BERSIH-DESA DI DESA TAWUN, KECAMATAN KASREMAN, KABUPATEN NGAWI, JAWA TIMUR - Cathrin, Shely (Jurnal Filsafat "WISDOM", 2017)
Bersih-Desa in Tawun village is an individual expression and collective interaction of the society which have the quality of traditional agrarian, therefore the presence of this ceremony cannot be separated from the socio-cultural’s parts and activities of the society. There are some valuable reasons behind this question why this ceremony still exists until this present day, the main reason is because the ceremony has some elements and cultural factors and also some virtuous values which then give such a good live guide to their generation. The method of this research is ‘hermeneutics philosophical’. This research is done by combining the library research which is reinforced with the direct observation. The results of this research is the existence of a cultural philosophy concept of the ritual ceremony ‘Bersih-Desa’ in Tawun village including its elements and determinant factors that caused in the presence of the ceremony until this present-day and also there are society understanding toward this ceremony. This ritual ceremony implements some values and virtuous attitudes which then it can be done by the society because it gives some positive impacts for their development. The society is highly expected for not only able to understand the values which are consisted in its ceremony, but they have also able to use it in their daily life.